Harassment of women garment workers in Bangladesh (Journal of the Bangladesh Agricultural University, 2011)
The study analyzed the different factors that are responsible for the harassment of women garment workers in Bangladesh. Three garment factories from Mirpur area under Dhaka district were selected purposively where garment factories are available. The sample consisted of 90 women workers taking 30 randomly from each of the three garment factories. Female workers are mostly employed at the lower category of jobs like operator, finishing helper, polyer etc. These jobs are very monotonous in nature. Because of the nature of their jobs, female workers sometimes lose interest in work and become depressed. A large number of female workers received low and irregular wages which create their job dissatisfaction. Only 22 female workers earned salary between Tk. 2700 to Tk. 3000 per month. Female workers are sexually harassed by their co-workers in the factory or by police or by mastans in the street. Communication problem is a major problem faced by most of the female garment workers. A long distance travel is not only physical strenuous but also mentally stressful. Their overtime rate is very low. Long working hours result in a number of illnesses and diseases like headache, eye trouble, ear ache, musculoskeletal pain etc. Women are exploited easily due to lack of technical knowledge and training. The employers do not pay any heed to this exploitation. Keywords: Garment industry; Women workers; Harassment DOI: 10.3329/jbau.v8i2.7940 J. Bangladesh Agril. Univ. 8(2): 291-296, 2010